Datos sobre la flora y vegetación de la Serranía de Ronda (Málaga, España) (Acta Botanica Malacitana, 1998)
New data on flora and vegetation in the Serranía de Ronda (Málaga, Andalusia, Spain). A floristic and phytosociologial study has been done in the Natural Park Sierra de las Nieves, placed in Málaga (Andalusia, Spain). A total of 1.400 taxa have been recorded, fom which we have pointed out and commented 36, due to their biological value as endemisms, rare, protected or endemic species or new records in the studied area. One new taxonomical combination is proposed: Ulex baeticus subsp. bourgaeanus. A total of 78 associations and communities have been recorded. New sintaxa are described: one alliance (Pino pinastri-Juniperion phoeniceae), 12 associations, 9 subassociations and one new combination. The 6 climactic series described with their main tree species, soil and bioclimatic range are the following: two series of Quercus suber (termo-mesomediterranean on schists), one of Quercus rotundifolia (mesomediterranean on limestones), one of Quercus pyrenaica (mcsomediterranean on schists), one of Quercus alpestris (supramediterranean on limestones) and one of Juniperus sabina (oromediterranean on limestones). The 5 edaphoxeric series described with their main tree species, soil and bioclimatic range are the following: two series of Abies pinsapo (meso-supramediterranean on perdotite rocks and dolomite), two series of Juniperus phoenicea (termo-meso-supramediterranean on marble, dolomite and limestones) and one of Pious pinaster (termo-mesomediterranean on peridotite rocks). The 5 riverine edaphoseries described with their main tree species, soil and water-level range are the following: one of Fraxinus angustifolia (summer-droughted rivers on limestones), two of Salix pedicellata (summer-droughted rivers on peridotite rocks, schists and limestones) and two of Nerium oleander (seasonal streams, on peridotite rocks, schists and limestones). Finally, the complete sintaxonomic scheme, with new sintaxa, combinations, hierarchycity and comments on the associations and communities is given